2016
DOI: 10.1002/cmdc.201600115
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Diverse Small‐Molecule Inhibitors of Mammalian Sterile20‐like Kinase 3 (MST3)

Abstract: Increasing evidence suggests key roles for members of the mammalian Sterile20-like (MST) family of kinases in many aspects of biology. MST3 is a member of the STRIPAK complex, the deregulation of which has recently been associated with cancer cell migration and metastasis. Targeting MST3 with small-molecule inhibitors may be beneficial for the treatment of certain cancers, but little information exists on the potential of kinase inhibitor scaffolds to engage with MST3. In this study we screened MST3 against a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 46 publications
0
43
0
1
Order By: Relevance
“…43 The gene encoding human Myt1 kinase domain (Myt1-KD, residues 75–361) cloned in-frame with an N-terminal His 6 tag was received in a pNIC28-Bsa4 vector from Addgene (plasmid 39061). The gene encoding full-length Escherichia phage lambda serine/threonine-protein phosphatase (LAMBD, residues 1–221) was synthesized by GeneArt with optimized codon usage for E. coli protein expression and subcloned into pGEX-6p-2 vector with N-terminal GST tag.…”
Section: Methodsmentioning
confidence: 99%
“…43 The gene encoding human Myt1 kinase domain (Myt1-KD, residues 75–361) cloned in-frame with an N-terminal His 6 tag was received in a pNIC28-Bsa4 vector from Addgene (plasmid 39061). The gene encoding full-length Escherichia phage lambda serine/threonine-protein phosphatase (LAMBD, residues 1–221) was synthesized by GeneArt with optimized codon usage for E. coli protein expression and subcloned into pGEX-6p-2 vector with N-terminal GST tag.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it has been reported that indole-based compounds are inhibitors of serine/threonine-protein kinase B-raf (BRAF) 50 , 51 , B-cell lymphoma 6 (BCL-6) 52 , proto-oncogene tyrosine-protein kinase Src (c-Src) 53 , 54 and poly (ADP-ribose) polymerase (PARP) 55 , in clear agreement with our model. Similarly, indazole-based derivatives have been reported as inhibitors of BRAF 56 , phthalazinone core is present in inhibitors of PARP 57 , as well as quinoline scaffold is common in molecules acting as c-Src 58 and mammalian sterile20-like protein kinase 3 (MST3) inhibitors 59 . These evidences validate our iVS method in order to enable the identification of suitable targets for a particular molecular library, foreseeing successful biological investigation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the efficacy of using ALK inhibitors in advanced nonsmall cell lung cancer with ALK rearrangement is evident in clinical trials . A study by Olesen et al identified 14 inhibitors, eight of which are in clinical trials or are Food and Drug Administration approved, that inhibited the enzymatic activity of STK24. Although further detailed investigations are required, STK24‐selective inhibitors are potential cancer therapeutics in tumours harbouring STK24 rearrangements.…”
Section: Discussionmentioning
confidence: 99%